2016
DOI: 10.3324/haematol.2015.132761
|View full text |Cite
|
Sign up to set email alerts
|

The immune microenvironment in Hodgkin lymphoma: T cells, B cells, and immune checkpoints

Abstract: Leaders in Hematology review seriesdriven by a combination of selective recruitment as well as intratumoral functional reprogramming. 16 RS cells produce a variety of Th2 and Treg-selective chemoattractants, including CCL17/TARC,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 127 publications
(112 reference statements)
3
103
0
4
Order By: Relevance
“…Classical Hodgkin lymphoma (cHL) is a unique neoplasia characterized by only 1% of malignant Reed‐Sternberg (RS) cells surrounded by a reactive cellular background. Recent evidence has shown that interaction of ligands is expressed by RS cells with immune checkpoint receptors expressed by T cells in the tumor microenvironment, thereby promoting T cell exhaustion and is thus an ineffective immune response . PD‐1 is an inhibitory receptor expressed on activated T cells found in tumor microenvironment.…”
Section: Clinical Parameters and Distribution Of Chl Patients At Diagmentioning
confidence: 99%
“…Classical Hodgkin lymphoma (cHL) is a unique neoplasia characterized by only 1% of malignant Reed‐Sternberg (RS) cells surrounded by a reactive cellular background. Recent evidence has shown that interaction of ligands is expressed by RS cells with immune checkpoint receptors expressed by T cells in the tumor microenvironment, thereby promoting T cell exhaustion and is thus an ineffective immune response . PD‐1 is an inhibitory receptor expressed on activated T cells found in tumor microenvironment.…”
Section: Clinical Parameters and Distribution Of Chl Patients At Diagmentioning
confidence: 99%
“…14 Immunohistochemistry and gene-expression profiling of pretreatment whole-tissue biopsies have identified prognostic biomarkers that, although not well validated, have been used to stratify risk in some patients. 15 By using NanoString technology (digital expression profiling on formalin-fixed paraffin-embedded tissue), a 23-gene outcome predictor was generated by using samples from adults enrolled on the Eastern Cooperative Oncology Group E2496 trial.…”
Section: Hlmentioning
confidence: 99%
“…The abundance of IgG4+ plasma cells in NSHL and IgG4‐RD suggests that the immunological microenvironment in both diseases may be similar. The exact mechanism in NSHL allowing HRS cells to escape the patient's own immune system remains unknown . Production of cytokines, such as IL‐4, IL‐5 and IL‐13, have been implicated to cause attraction of plasma cells and eosinophils and TGF‐β and IL‐10 may contribute to fibrosis .…”
Section: Discussionmentioning
confidence: 99%